Facilitating gender-affirming participatory visual research in embodied and online spaces. Issue 1 (15th March 2022) - Burkholder, Casey; Thorpe, Amelia; Swell, Pride/
Abstract : How might participatory visual research with 2SLGBTQ+ be facilitated in gender affirming ways across physical and digital spaces? What do these practices look like, and how might facilitators adapt their practices in response to cisnormative language and binary physical spaces? This article describes the opportunities and challenges to facilitating two projects with 2SLGBTQ+ youth. The first project, Where Are Our Histories (2018–2020) – was a face-to-face participatory visual research project addressing the erasure of 2SLGBTQ+ people, experiences, and histories from the New Brunswick Social Studies curricula and classrooms and co-creating media to interrupt these erasures with youth. We consider the ways that participatory visual research can be facilitated with 2SLGBTQ+ youth in embodied spaces that are gender-affirming and resist tokenism and structural violence by employing DIY (do it yourself) strategies. We describe the ways in which facilitating Where Are Our Histories has shaped the co-facilitation strategies employed in a distance-based participatory visual research project, Pride/Swell, with 50 2SLGBTQ+ youth amidst Covid-19. We describe how both projects required engaged attention to facilitating the public-facing visual outputs (zines, collages, cellphilms) in public spaces. We offer strategies for facilitating and negotiating cisnormative, transphobic, and homophobic discourses in person and online.